Land your dream career : eleven steps to take in college (Lanham, Maryland : Rowman & Littlefield Publishers, 2013)
Obtaining a college degree does not automatically result in a job, let alone a dream career. The authors show readers what they can do in college to successfully pave the way for future employment, and provide easy-to-follow strategies for effectively using time on campus to start building a career.
Start now -- Design, build, and protect your brand -- Immerse yourself inside and outside the classroom -- Employ the magic of 75/25 -- Master every conversation -- Innovate to stand out -- Allow for wiggle room and celebration -- Network, network, network -- Use new media tools -- Become an expert -- Put it all together.
Includes index.
Keywords: College graduates -- Employment; College graduates -- Employment